Minimum Miscibility Pressure Investigation for Carbon Dioxide Injection with Different Malaysian Light Oil Samples - Juan, Saw Li (Universiti Teknologi Petronas, 2012)
As the global demand for oil continues to rise, relying on primary and secondary oil recovery methods alone are just inadequate. In Malaysia, there is approximately one billion barrels of oil that can still be produced through enhanced oil recovery (EOR) techniques. One of the tertiary oil recovery techniques that are implemented is the carbon dioxide (CO2) flooding. Carbon dioxide flooding has been applied globally as miscible, near miscible or immiscible flooding, depending on the reservoir characteristics and oil composition. By measuring the minimum miscibility pressure (MMP), the mode of the displacement can be determined if it is miscible or immiscible. The purpose of this project is to investigate the CO2 MMP of different Malaysian light oil samples by using the Vanishing Interfacial Tension (VIT). Published correlations were then referred to and compared with the experiments’ results. This study has found that the CO2 MMP for Angsi and Dulang are 3077 psia and 2957 psia respectively. In comparison the experimental results with several published correlations, (Cronquist, 1977) correlation gave the best predicted MMP for both reservoir oil. The effects of each parameters that affects CO2 MMP for instance, reservoir temperature and oil composition were discussed in this paper. This study has also demonstrated the reliability of the VIT technique in predicting MMP by pendant drop method experiments in comparison with the other published correlations.